Strategi Pengelolaan Konten pada Akun Instagram @syca.official dalam Membangun Customer Engagement - Evita, Jeanette; Diana Amalia (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
Instagram plays a very strong role, especially in the era of digital marketing. There are many features that support the growth of a brand in an industry, particularly in the beauty industry. Beauty industry has a very ripid development, especially with the emergence of various new products that are increasingly tailored to Indonesian consumers. The rapid development of trends and cosmetic products makes digital marketing era increasingly popular. Moreover, currently social media, especially Instagram has supported influential trends in digital marketing. @syca.official has become one of the local cosmetic brands that has grown significantly and plays special role in this Indonesian beauty industry. Not only does @syca.official market products through digital campaigns, but it also serves as a community platform for women and beauty enthusiasts to share information, reviews, and support each other through their created content. Among the many local cosmetic brands that continue to grow, @syca.official stands out with its unique content concept and campaigns, thereby enhancing customer engagement.  In executing this strategy, @syca.official employs several methods, starting from sharing more relevant content, optimizing content quality according to the target audience and current trends, structuring content flow based on consumer interests, and fostering a connection between the brand and its consumers.